A SUNCT‐like headache associated with lateral pontine infarction – case series and systematic review - Priabprat Jansem; Nattapat Watanapa; Sekh Thanprasertsuk; Wanakorn Rattanawong; Thanakit Pongpitakmetha; Prakit Anukoolwittaya (European Journal of Pain, 2024)
BACKGROUND AND AIM: Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing (SUNCT) and autonomic symptoms (SUNA) are trigeminal autonomic cephalalgias (TACs). The study explores the potential association between SUNCT/SUNA-like headaches and lateral pontine infarctions. METHODS: Case series and systematic review. RESULTS: We present three cases diagnosed with SUNCT following lateral pontine infarction on magnetic resonance imaging (MRI), along with a review of these cases and 10 others from the literature. DISCUSSION AND CONCLUSION: This review suggests a connection between SUNCT/SUNA-like symptoms and lateral pontine infarctions. The section also delves into the anatomy and pathophysiology of these symptoms, proposing a mechanism involving neural pathway remodelling in the lateral brainstem.
Keywords: Migraine and Headache Studies; Pain Management and Treatment; Pain Mechanisms and Treatments